2016
DOI: 10.1038/nature16504
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced extinctions in the gut microbiota compound over generations

Abstract: The gut is home to trillions of microbes that play a fundamental role in many aspects of human biology including immune function and metabolism 1,2. The reduced diversity of the Western microbiota compared to populations living traditional lifestyles presents the question of which factors have driven microbiota change during modernization. Microbiota accessible carbohydrates (MACs) found in dietary fiber, play a key role in shaping this microbial ecosystem, and are strikingly reduced in the Western diet relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
1,061
6
26

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,413 publications
(1,120 citation statements)
references
References 26 publications
27
1,061
6
26
Order By: Relevance
“…In the human gut, there are trillions of microorganisms which together are known as microbiota 3,4 . Intestinal bacteria have the highest concentration, approximately 100 trillion, with a density of 9x10 [13][14] and considerable biodiversity (approximately 1000 bacterial species).…”
Section: Microbiotamentioning
confidence: 99%
“…In the human gut, there are trillions of microorganisms which together are known as microbiota 3,4 . Intestinal bacteria have the highest concentration, approximately 100 trillion, with a density of 9x10 [13][14] and considerable biodiversity (approximately 1000 bacterial species).…”
Section: Microbiotamentioning
confidence: 99%
“…It has been suggested that diet may be the easiest way to alter the host microbiota and that such changes may come about rapidly (Wu et al, 2011). However, a recent study in rodents suggests this may not be as easy as it seems (Sonnenburg et al, 2016). They raised mice in a germ-free (GF) environment and then transplanted a human microbiota.…”
Section: Adult Microbiotamentioning
confidence: 99%
“…It has been proposed that individuals with more diverse gut microbiota are more adept at responding to environmental challenges (54), such as resisting colonization of gut pathogens by competitive exclusion (i.e., commensal bacteria take over niches and/or consume substrates to inhibit the growth of pathogenic bacteria) (55). Interestingly, mice fed low-fiber diets showed decreased microbial diversity, which could be recovered after the introduction of a high-fiber diet; however, after generations of feeding a low-fiber diet, microbial diversity could not be recovered after the re-introduction of fiber (56). This finding may have implications to our current population, because DF consumption has decreased since the industrial revolution (57).…”
Section: Introductionmentioning
confidence: 99%